The calmodulin fused kinase novel gene family is the major system in plants converting Ca2+ signals to protein phosphorylation responses - Fei Chen (Nature Portfolio, 2017)
Abstract Eukaryotes utilize Ca2+ as a universal second messenger to convert and multiply environmental and developmental signals to downstream protein phosphorylation responses. However, the phylogenetic relationships of the genes that convert Ca2+ signal (CS) to protein phosphorylation responses (PPRs) remain highly controversial, and their origin and evolutionary trajectory are unclear, which greatly hinders functional studies. Here we examined the deep phylogeny of eukaryotic CS converter gene families and identified a phylogenetically and structurally distinctive monophyly in Archaeplastida. This monophyly can be divided into four subfamilies, and each can be traced to ancestral members that contain a kinase domain and a calmodulin-like domain. This strongly indicates that the ancestor of this monophyly originated by a de novo fusion of a kinase gene and a calmodulin gene. This gene family, with a proposed new name, Calmodulin Fused Kinase (CFK), had expanded and diverged significantly both in sizes and in structures for efficient and accurate Ca2+ signalling, and was shown to play pivotal roles in all the six major plant adaptation events in evolution. Our findings elucidated the common origin of all CS-PPR converter genes except CBL-CIPK converter genes, and revealed that CFKs act as the main CS conversion system in plants.